Upaya Guru Dalam Menerapkan Tata Tertib Terhadap Siswa Kelas IV Sekolah Dasar Negeri 15 Emang Raya - Sari, Lusi Bulan; Asep Eka Nugraha; Kasihani Lestari (STKIP Melawi, 2025)
Abstract: This study aims to determine the teacher’s efforts in implementing school rules for fourth-grade students at SDN 15 Emang Raya. The research uses a qualitative descriptive method. The subjects of the study include the classroom teacher, principal, and fourth-grade students, while the object is the teacher’s efforts in enforcing student discipline. Data were collected through observation, interviews, and documentation, using observation sheets, interview guides, and documentation forms as instruments. Data analysis involved data collection, reduction, presentation, and conclusion drawing, while data validity was tested through source and technique triangulation. The results show that teachers play active roles as educators, instructors, guides, mentors, trainers, and evaluators in implementing student discipline. These efforts include fostering responsibility, orderliness, punctuality, and cleanliness. Overall, the implementation of school rules has been effective; however, the aspects of mentoring and training students still need to be improved. Keywords: Teacher Efforts, School Rules, Elementary Students Abstrak: Penelitian ini bertujuan untuk mengetahui upaya guru dalam menerapkan tata tertib terhadap siswa kelas IV di SDN 15 Emang Raya. Metode yang digunakan adalah kualitatif dengan jenis deskriptif. Subjek penelitian meliputi guru kelas, kepala sekolah, serta siswa kelas IV, sedangkan objek penelitian adalah upaya guru dalam penerapan tata tertib siswa. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi dengan instrumen berupa lembar observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahap pengumpulan, reduksi, penyajian, dan penarikan kesimpulan, sedangkan keabsahan data diuji menggunakan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa guru berperan aktif sebagai pendidik, pengajar, pengarah, pembimbing, pelatih, dan evaluator dalam menerapkan tata tertib siswa. Upaya tersebut meliputi pembiasaan tanggung jawab, ketertiban, kedisiplinan, dan kebersihan. Secara keseluruhan, penerapan tata tertib berjalan efektif, namun pembimbingan dan pelatihan siswa masih perlu ditingkatkan. Kata Kunci: Upaya Guru, Tata Tertib, dan Siswa Sekolah Dasar.